Assessment of the genetic diversity of durum wheat cultivars (Triticum durum Desf.) using microsatellite markers (Experimental biology, 2018)
Durum wheat (Triticum durum Desf.) is an important crop both in the world and in Kazakhstan.  Durum wheat is used as a valuable raw material in bakery and pasta production. Effective breeding strategies require knowledge of the genetic diversity level of cultivars. Polymorphism of the twenty-nine durum cultivars was analyzed using 7 microsatellite markers. The total number of alleles was 20 and the effective allele number was an average of 2.8. The average polymorphic information content (PIC) value was 0.3658 and ranged from 0.1267 in Xgwm219 to 0.5457 in Xgwm247. The genetic diversity indices of Shannon and Nei were equal to 0.7174, 0.4243, respectively. The level of genetic diversity was relatively high. The genetic distance between cultivars was calculated. Also, with the help of microsatellite markers, a cluster analysis of the studied cultivars was conducted. The results of the study make it possible to assess the level of genetic polymorphism in the studied cultivars and indicate that the used markers are informative. Polymorphic markers were selected for the following studies on the durum genetic diversity. The obtained information will be used in breeding programs aimed at increasing yield and adaptability of durum wheat.Key words: Triticum durum, genetic resources, genetic diversity, microsatellites, SSR.